Flooding and Elevation: An Examination of Differential Price Responses to Flood Events - Calvin Blackwell; Chris Mothorpe; Julie Wright (Journal of Sustainable Real Estate)
Although many studies show elevating properties in flood-prone areas can be cost effective, few, if any, studies have examined the impact of home elevation on property values. We examine the impact of multiple flood events on property values of elevated and non-elevated homes in Charleston, SC. We find flooding significantly reduces the rate of appreciation, and home elevation increases the rate of lost appreciation. Our results suggest home elevation is not a flood risk adaptation and mitigation strategy valued by the market.